Generating trajectories with temporal constraints for an autonomous robot - Silva, Jorge Bruno (2010)
Trajectory modulation and generation are two fundamental issues in the path planning problem in autonomous robotics, specially considering temporal stabilization of the generated movements. This is a very critical issue in several robotic tasks including: catching, hitting, and human-robot scenarios. In this work, we address these problems and focus on generating movement for a mobile robot, whose goal is to reach a target within a constant time. We use an Hopf oscillator whose solution controls velocity, adapted according to temporal feedback. We have also proposed an adaptive mechanism for frequency modulation of the velocity profile that enables setting different times for acceleration and deceleration. This approach is demonstrated on a DRK8000 mobile robot in order to confirm the system’s reliability with low-level sensors.